Value of using ultrasonic shears in reducing seroma formation after axillary lymph node dissection in breast cancer patients - Yousra Mohsen Elshoura; Ahmed Refaat; Basma Hussein Abdelaziz Hassan; Philobater Bahgat Adly Awad; Mohamed Wael Ahmed; Sherif Mokhtar; Emad Salah El din Khalaf (Journal of the Egyptian National Cancer Institute)
Abstract Background Axillary lymph node dissection (ALND) is an essential step in the management of breast cancer. ALND is conventionally performed using radio frequency electrosurgery. The post-operative complications of utilizing such energy (such as prolonged drainage time, seroma, or infection) lead to prolonged recovery. Hence, it may delay the initiation of adjuvant chemo/radiotherapy for this critical category of patients. Using ultrasound shears provides a wide spectrum of tissue effects via mechanical oscillation. The absence of an electric circuit in ultrasound shears reduces thermal injury and accordingly cellular damage. Objective Comparing utilization of ultrasound shears in axillary lymph node dissection to conventional radio frequency electrosurgery in terms of operative time, post-operative drainage amount and days, post-operative pain, the incidence of seroma or infection, and lymph node yield. Methods This study is a randomized control trial. It includes 56 breast cancer ALND cases performed in conjunction with either BCS or MRM; being upfront surgery cases or post-neoadjuvant therapy cases, 28 patients underwent ALND using ultrasound shears and 28 underwent ALND using radio frequency electrosurgery. Results The mean age of the study population was 51 ± 11.7 years, with a mean BMI of 39. The mean operative time in the ultrasound shear group was 29.4. ± 7.6 min and 31.6 ± 5.1 min in the conventional group. The mean amount of drainage in the ultrasound shear group was 319.6 ± 75.4 ml and 407.5 ± 75.2 ml in the conventional group. The mean drainage days in the ultrasound shear group were 8 ± 1 day and 12 ± 2.2 days in the conventional group. Seroma formation was recorded in 6 of the ultrasound shear groups and 9 in the conventional group. Seroma followed by infection was found in 10% of the ultrasound shear group versus 21% in the conventional group. Seroma formation and wound infection were significantly related to the conventional group (p-value = 0.01). Conclusion Our study recommends the utilization of ultrasound shears in ALND as it is a safe and accurate method that allows faster post-operative recovery with shorter drainage time and lower incidence of seroma or infection, without affecting operative time or lymph node yield. Trial registration Trial no.: PACTR202402831197428. Date of approval: 19/02/2024